SERBIAN LAUNDROMAT - Krstic, Jovan (Revista Direitos Humanos Fundamentais, 2019)
Laundromat is a complex system for laundering money stolen from the government by corrupt politicians or earned through organized crime activity. It was designed to not only move money from Serbian shell companies into EU banks through many countries, but it had the added feature of getting corrupt or uncaring judges and sequesters on the secret funds in those countries to legitimize the funds. Serbian Laundromat works on the principle "good morning to all four sides of the World", also exploiting the "neutrality" on the origin and amount of money that comes from abroad or being collected from own people (placement), put abroad (layering) and returned back as "foreign" investment (integration). Some Case Studies has been done on the institutional response to the corruption challenge (that missing in Serbia).